Chronotopes of the City: Spatial Injustice and Narrative Form in Helena María Viramontes’s Their Dogs Came with Them - Rubóczki, Babett (Hungarian Journal of English and American Studies, 2021)
Combining Mikhail Bakhtin’s concept of the chronotope and Sarah Dillon’s notion of the palimpsest, the essay highlights the dialogic relationship between narrative time and space in Chicana author Helena María Viramontes’s novel, Their Dogs Came with Them (2007). Set in East Los Angeles in the 1960s and 1970s—the heyday of urban renewal projects and the rapid spread of freeways—the novel registers the geographical displacement and constrained socio-economic mobility of Mexican Americans whose homes are demolished by the freeway building bulldozers. The spatial form of intersectionality characterizing the architectural structure of the freeways also describes the narrative form of the novel. The non-linear narrative is structured upon multiple intersecting plotlines, each of which portrays the social struggles of a young Chicana woman inhabiting the city. Focusing on the interplay of environmental theme and narrative form, the paper explores the narrative representation of East Los Angeles as a spatially and temporally multilayered landscape that palimpsestously overlays and interconnects the personal memory of the characters and the collective history of Mexican Americans’ socio-political oppression in North America. (BR)